Effect of Psychotropic Medications on Hammertoe Reconstruction Outcomes. Issue 3 (24th August 2020) - Maidman, Samuel D.; Nash, Amalie E.; Fantry, Amanda; Tenenbaum, Shay; Daoud, Yahya; Brodsky, James; Bariteau, Jason T.
Background: Hammertoe deformities can seriously affect activity level and footwear. The use of prescription, mood-altering medications is very common, with some estimates as high as 25% of the population. Mood disorders, especially depression, negatively affect the results of medical and operative treatments. This study assessed the relationship of mood-altering medication use with the outcomes and complications of operative reconstruction of hammertoes. Methods: Data were prospectively collected from 116 patients who underwent hammertoe reconstruction, including demographic information, medical history, the use of mood-altering psychotropic medications (antidepressants, anxiolytics, hypnotics, and mood stabilizers), and postoperative complications. Preoperative patient-reported outcomes were measured using the visual analog scale (VAS) for pain and Short Form Health Survey (SF-36), which were repeated at 1-year follow-up. Results: A total of 36.2% of patients were taking psychotropic medications. Medication and nonmedication groups had similar pain VAS and SF-36 Physical Component Summary (PCS) scores before and after surgery. Compared with nonmedication patients, patients on psychotropic medications had significantly lower SF-36 Mental Component Summary (MCS) scores preoperatively ( P = .001) and postoperatively( P = .006), but no significant difference in the change in MCS (ΔMCS) from preoperative to postoperative. Psychotropic medication use was associated with superficial wound infections ( P = .048), but not other complications. Conclusions: Patients taking psychotropic medications were equally likely to benefit from forefoot reconstruction as nonmedication patients. Preoperative and postoperative PCS and VAS were not significantly different between medication and nonmedication groups. Although the medication group had lower absolute MCS, they reported the same magnitude of improvement in MCS (ΔMCS) as the nonmedication group. Level of Evidence: Level II, prospective cohort study.